KINEMATIC DEMANDS OF TWO SMALL-SIDED GAMES OF COSTA RICAN COLLEGE SOCCER PLAYERS - Rojas-Valverde, Daniel Francisco; Morera-Castro, María; Montoya-Rodríguez, Jaqueline; Gutiérrez-Vargas, Randall (Pensar en Movimiento: Revista de Ciencias del Ejercicio y la Salud, 2017)
The purpose of this paper was to compare two small-sided games kinematics of Costa Rican college soccer players. Two SSG (2x10min, 3 min rest in between), C1 (600m2) and C2 (1200m2), were played by 14 college soccer players of Costa Rica. Global Positioning System was used to measure kinematic and physiological variables in both conditions. A mixed ANOVA was used, results suggested C1 and C2 were statistically different in speed (C1 < C2), distance (C1 < C2) and heart rate (C1 > C2). When analyzing the distance covered by speed category (low, moderate and high running actions) results suggest C2 had higher intensities compared to C1. This research confirms the findings of previous studies on the effectiveness of SSG to simulate real game conditions in short periods of time. Conclusions: C2 had higher intensities compared to C1 game with lower physiological demand. Likewise, the C2 resembles more accurately matches in official conditions of Costa Rican players.